Oracle8 PL/SQL programming - Urman, Scott (Osborne McGraw-Hill, 1997)
In addition, author reviews Oracle technical documentation, writes white papers on Oracle languages, and makes technical presentations both inside Oracle and at meetings of Oracle User's Groups. Scott is the best-selling author of Oracle Press' Oracle PL/SQL Programming and Oracle8 PL/SQL Programming